A population-based study on incidence, treatment, and survival in ampullary cancer in the Netherlands. Issue 7 (July 2021) - de Jong, Evelien J.M.; Geurts, Sandra M.E.; van der Geest, Lydia G.; Besselink, Marc G.; Bouwense, Stefan A.W.; Buijsen, Jeroen; Dejong, Cornelis H.C.; Heij, Lara R.; Koerkamp, Bas Groot; de Hingh, Ignace H.J.T.; Hoge, Chantal; Kazemier, Geert; et al.
Abstract: Introduction: Ampullary cancer is rare and as a result epidemiological data are scarce. The aim of this population-based study was to determine the trends in incidence, treatment and overall survival (OS) in patients with ampullary adenocarcinoma in the Netherlands between 1989 and 2016. Methods: Patients diagnosed with ampullary adenocarcinoma were identified from the Netherlands Cancer Registry. Incidence rates were age-adjusted to the European standard population. Trends in treatment and OS were studied over (7 years) period of diagnosis, using Kaplan-Meier and Cox regression analyses for OS and stratified by the presence of metastatic disease. Results: In total, 3840 patients with ampullary adenocarcinoma were diagnosed of whom, 55.0% were male and 87.1% had non-metastatic disease. The incidence increased from 0.59 per 100, 000 in 1989–1995 to 0.68 per 100, 000in 2010–2016. In non-metastatic disease, the resection rate increased from 49.5% in 1989–1995 to 63.9% in 2010–2016 (p < 0.001). The rate of adjuvant therapy increased from 3.1% to 7.9%. In non-metastatic disease, five-year OS (95% CI) increased from 19.8% (16.9–22.8) in 1989–1995 to 29.1% (26.0–31.2) in 2010–2016 (logrank p < 0.001). In patients with metastatic disease, median OS did not significantly improve (from 4.4 months (3.6–5.0) to 5.9 months (4.7–7.1); logrank p = 0.06). Cancer treatment was an independent prognostic factor for OS among all patients. Conclusion: Both incidence and OS of ampullary cancer increased from 1989 to 2016 which is most likely related to the observed increased resection rates and use of adjuvant therapy. Highlights: Over time, the incidence of ampullary cancer in the Netherlands increased. Resection was 50% of non-metastatic disease in 1989–1995 and 64% in 2010–2016. Five-year overall survival increased from 20% to 29% in non-metastatic disease. Treatment choices and overall survival in metastatic disease were similar over time.